2010
DOI: 10.1002/jsfa.4149
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physicochemical and sensory changes in fresh and frozen herring (Clupea harrengus L.) during marinating

Abstract: These results suggest that the semi-marinades from raw fish are characterised by higher sensory quality, better colour parameters and higher yield than those from frozen thawed fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 25 publications
3
34
1
2
Order By: Relevance
“…These results are in agreement with previous reports showing that both DM and protein content in brines from marinated herring changes significantly within the first 200 days of the ripening period and thereafter these leveled off [16]. The generally high DM content found in the brines was expected as it has been shown that up to 30% of the raw herring weight is lost during marinating whole carcasses and fillets [15], and thus biomolecules leak into the brine during marination. The volume and concentration of biomolecules in the brines depend mainly on the raw fish composition, additives used, processing water quality and process operations.…”
Section: Proximate Composition Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with previous reports showing that both DM and protein content in brines from marinated herring changes significantly within the first 200 days of the ripening period and thereafter these leveled off [16]. The generally high DM content found in the brines was expected as it has been shown that up to 30% of the raw herring weight is lost during marinating whole carcasses and fillets [15], and thus biomolecules leak into the brine during marination. The volume and concentration of biomolecules in the brines depend mainly on the raw fish composition, additives used, processing water quality and process operations.…”
Section: Proximate Composition Analysissupporting
confidence: 92%
“…Total nitrogen and protein content were used to deduce and estimate the amount of non-protein nitrogen in our samples (values from Table 3 and a Kjeldahl factor of 6.25). The values found by Szymczak [15] were higher than the levels found in this study for TSa and SC, which are reported here to be 4.16 g/kg and 0.78 g/kg for whole herring and fillets, respectively. As stated in the materials and methods, TSa and TSp are placed in the brine first as whole fish and subsequently as fillets, whereas SC and VC are filleted prior to brining, and for this reason it was expected that the level of biomolecules leaking from the herrings into the brine would be higher in TSa and TSp, with leaking of blood protein first and muscle protein in the later stage.…”
Section: Proximate Composition Analysiscontrasting
confidence: 83%
See 1 more Smart Citation
“…In Europe, cold marinating makes up about 92% of the market (Szymczak, 2011). It is carried out by first curing fish in a proper marinade solution of vinegar and salt for up to 12 weeks, depending on the products.…”
Section: Marinating Methodsmentioning
confidence: 99%
“…Most frequently they include formation of ice crystals resulting in a local increase of salt concentration. The influence of freezing on fish muscle proteins mainly concerns the changes in solubility of protein fractions, their water-holding capacity, and the activity of proteolytic enzymes (Szymczak 2011). Freezing causes disruption and separation of muscle fibre bundles due to the occurrence of numerous extracellular and intracellular ice crystals.…”
mentioning
confidence: 99%